1992
DOI: 10.1116/1.578002
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–carbon bond forming reactions on Cu(110) surfaces

Abstract: The coupling of one-carbon (C]) fragments to form carbon-carbon bonds has been studied on a Cu(11O) surface. In these studies, methyl (CH 3 ) and methylene (CH 2 ) groups have been generated on Cu( 110) by the dissociative adsorption of CH3I and CH 2 I 2 , respectively. Formation of CH 3 (a) below 200 K on this surface is inferred from the lack of molecular desorption as well as the lack of recombinative hydrogen desorption in temperature-programmed reaction (TPR) experiments. Similar low temperature C-I bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 0 publications
2
41
0
Order By: Relevance
“…In contrast, the direct coupling of methylene surface species does not involve any hydrogenation-dehydrogenation steps. Coupling such as this is actually more typical of late transition metals [62], and has been reported for methylene on Cu(1 1 0) [63], Pd(1 0 0) [24], and Rh(1 1 1) [27], and for other alkyls on Cu(1 1 1) [64], Ag(1 1 1) [65], and Au(1 1 1) [66], among others.…”
Section: N(e) / Hzmentioning
confidence: 87%
“…In contrast, the direct coupling of methylene surface species does not involve any hydrogenation-dehydrogenation steps. Coupling such as this is actually more typical of late transition metals [62], and has been reported for methylene on Cu(1 1 0) [63], Pd(1 0 0) [24], and Rh(1 1 1) [27], and for other alkyls on Cu(1 1 1) [64], Ag(1 1 1) [65], and Au(1 1 1) [66], among others.…”
Section: N(e) / Hzmentioning
confidence: 87%
“…The surface chemistry of diiodomethane has been investigated previously on several transition-metal surfaces including Cu, 24,25 Ag, [26][27][28] Mo, 29,30 Pd, 31,32 Pt, 33 Rh, 34,35 Ru, 36 and Ni. 37,38 Studies have also been performed on Al surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene production via coupling of methylene is also seen in Fig. 1, which is somewhat surprising since this is a reaction more common on coinage metals [23,52]. When starting from diiodomethane, iodomethane is produced as well on this V(100) surface, an indication that hydrogenation reactions compete kinetically with carbon-halogen dissociation steps.…”
Section: Surface Chemistry Of Methylene and Methyl Groupsmentioning
confidence: 78%
“…The growing alkyl chains can, at each stage of their growth, undergo disproportionation via b-hydride elimination to produce the corresponding alkene, and also reductive elimination with surface hydrogen to yield the appropriate alkane. In the UHV surface-science community this type of chain-growth reaction was first observed in experiments with coadsorbed methyl and methylene groups on copper surfaces [20,52]. In fact, we have reported that such carbon-carbon forming reactions are possible on Ni(110) even when starting with either diiodomethane [25] or iodomethane [42] alone: chain growth to up to C 4 products was observed on that surface (Fig.…”
Section: Surface Chemistry Of Methylene and Methyl Groupsmentioning
confidence: 82%